FACTORING POLYNOMIALS USING SYNTHETIC DIVISION

In this section, we use the synthetic division method that helps to factor a cubic polynomial into linear factors. If we identify one linear factor of cubic polynomial p(x) then using synthetic division we can get the quadratic factor of p(x). Further if possible one can factor the quadratic factor into linear factors.

Factor each of the following polynomials using synthetic division :

Example 1 :

x3 - 3x2 - 10x + 24

Solution :

By Substituting x = 2, we get the remainder 0.

So (x - 2) is a factor.

Then, 

x2 - x - 12 = x2 - 4x + 3x - 12

x2 - x - 12 = x(x - 4) + 3(x - 4)

x2 - x - 12 = (x + 3)(x - 4)

Therefore, the factors are (x - 2)(x + 3)(x- 4).

Example 2 :

2x3 - 3x2 - 3x + 2

Solution :

By substituting x = -1, we get the remainder 0.

So (x + 1) is a factor.

Then,

2x2 - 5x + 2 = 2x2 - 4x - x + 2

2x2 - 5x + 2 = 2x(x - 2) - 1(x - 2)

2x2 - 5x + 2 = (2x - 1)(x - 2)

Therefore, the factors are (x + 1)(2x - 1)(x - 2).

Example 3 :

-7x + 3 + 4x3

Solution :

-7x + 3 + 4x3  =  4x3 + 0x2 - 7x + 3

By substituting x = 1, we get the remainder 0.

So (x - 1) is a factor.

Then,

4x2 + 4x - 3 = 4x2 + 6x - 2x - 3

4x2 + 4x - 3 = 2x(2x + 3) - 1(2x + 3)

4x2 + 4x - 3 = (2x - 1)(2x + 3)

Therefore, the factors are (x - 1)(2x - 1)(2x + 3).

Example 4 :

x3 + x2 - 14x - 24

Solution :

By substituting x = -2, we get the remainder 0.

So (x + 2) is a factor.

Then,

x2 - x - 12 = x2 - 4x  + 3x - 12

x2 - x - 12 = x(x - 4) + 3(x - 4)

x2 - x - 12 = (x + 3)(x - 4)

Therefore, the factors are (x + 2)(x + 3)(x - 4).

Example 5 :

x3  - 7x + 6

Solution :

By substituting x = 1, we get the remainder 0.

So (x - 1) is a factor.

Then,

x2 + x - 6 = x2 + 3x  - 2x - 6

x2 + x - 6 = x(x + 3) - 2(x + 3)

x2 + x - 6 = (x + 3)(x - 2)

Therefore, the factors are (x - 2)(x + 3)(x - 1).

Example 6 :

x3 - 10x2 - x + 10

Solution :

By substituting x = 1, we get the remainder 0.

So (x - 1) is a factor.

Then,

x2 - 9x - 10 = x2 - 10x + 1x - 10

x2 - 9x - 10 = x(x - 10) + 1(x - 10)

x2 - 9x - 10 = (x + 1)(x - 10)

Therefore, the factors are (x + 1)(x - 10)(x - 1).

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Order of Operations Worksheet

    Jul 24, 24 03:02 AM

    orderofoperations1.png
    Order of Operations Worksheet

    Read More

  2. Order of Operations

    Jul 24, 24 03:01 AM

    order-of-operations.png
    Order of Operations - Concept - Solved Examples

    Read More

  3. PEMDAS Rule Worksheet

    Jul 24, 24 02:50 AM

    pemdas-rule-worksheet
    PEMDAS Rule Worksheet

    Read More